2001
DOI: 10.1038/sj.ijo.0801481
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of weight loss and maintenance during 2 years of treatment by sibutramine in obesity. Results from the European multi-centre STORM trial

Abstract: BACKGROUND:In this report we assess pre-treatment determinants of weight loss and maintenance outcome in The Sibutramine Trial of Obesity Reduction and Maintenance (STORM), a 2 y randomized, double-blind, placebo-controlled, European multicenter study examining the effect of sibutramine (Sib) on inducing and maintaining weight loss in obese subjects. MATERIAL: A total of 605 obese patients (BMI: 30 ± 45 kgam 2 ) of both gender were included from eight European centers and treated for 24 months. The patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
90
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 14 publications
15
90
1
8
Order By: Relevance
“…At 3 months, energy intake was reduced by 186 kcal and weight change associated with topiramate treatment correlated with lower baseline energy intake, energy intake reduction as well as with higher baseline leptin and rT 3 levels. As in our study and in the STORM trial 19 with sibutramine, baseline BMI significantly predicted weight loss maintenance in topiramate treated patients; baseline BMI remained the only factor correlating with weight loss after 1 y treatment with topiramate.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…At 3 months, energy intake was reduced by 186 kcal and weight change associated with topiramate treatment correlated with lower baseline energy intake, energy intake reduction as well as with higher baseline leptin and rT 3 levels. As in our study and in the STORM trial 19 with sibutramine, baseline BMI significantly predicted weight loss maintenance in topiramate treated patients; baseline BMI remained the only factor correlating with weight loss after 1 y treatment with topiramate.…”
Section: Discussionsupporting
confidence: 79%
“…Baseline body weight, mode of treatment and age explained only 9% of the variation in 24-month weight change in the STORM study. 19 Body weight or BMI at baseline predicted weight loss in several other studies on weight management. 10,12 In the STORM study, 19 baseline body weight, sex, age, resting metabolic rate, smoking history, previous attempts to lose weight and age of onset of obesity were included as predictors of weight change but psychobehavioral and nutritional parameters were not taken into account.…”
Section: Discussionmentioning
confidence: 97%
“…Pretreatment body weight is an important independent predictor of weight loss and slightly overweight women may not respond as well to a weight management program as women who are obese. 115 Nor do all women experience changes in cravings and in food intake related to the menstrual cycle. This review addresses whether hormonal changes affect different components of energy balance, such as food intake, but food intake can also affect hormones.…”
Section: Implications For Weight Management Programsmentioning
confidence: 99%
“…There have been numerous studies conducted with all of the obesity drugs on the market, and the weight losses average about 5-10% of initial body weight at 6 months to 1 year. An exception was the Sibutramine Trial of Obesity Reduction and Maintenance (STORM) trial with sibutramine, 48 carried on in multiple sites in Europe, which achieved a loss of about 13% of initial body weight, and a study by Wadden et al 49 that demonstrated a weight loss of 16.5% at 1 year with sibutramine, rigid diet and lifestyle modification. However, the study by Wadden et al 49 and most of the sites in the STORM trial used very low-calorie diets to achieve a large initial weight loss, so the data are not comparable to those of other trials.…”
Section: Discussionmentioning
confidence: 99%